Strategies of companies of interurban road transport of the travellers in West Africa: case of Niger - (:unkn) unknown (My University, 2010)
This thesis is registered in the perspective of a strategic diagnosis of the Transport sector Intercity Road of travellers (TRIV) in West Africa (case of Burkina Faso, Mali and Niger). The transport organization and the functioning of enterprises of the sector to the yardstick of globalization and the modernization is still inadequate. There are many difficulties identified at various levels of the system thus hindering the economic development of the sector. For West Africa, many studies and research have already been carried out on the system of urban transport and on the transport of goods with diagnostics and recommendations. However, the sub-sector of TRIV also has its importance and it should be taken into account in the schema of sub-regional integration in Africa. Our research shows that the analysis of TRIV must not be limited to its aspects regulatory and institutional and that it must integrate the companies as the key elements of the development of the sector. These are now faced the challenge of competition on the markets both the domestic that sub-regional passenger transport. The modernization of the sector and its subsequent development involve adjustments of craft businesses, changes in the organization and the conditions of operation of this activity. Our approach addresses in the first time, the current configuration of the market of TRIV The analysis highlights the indispensable complementarity of the offer of transport companies and craftsmen carriers. From this finding, models of potential strategies are developed for firms forced to competitiveness. However, in light of the organization of the market of TRIV in Niger, of the multiplicity of enterprises and absence of data, we defined groups contrasting of enterprises, the consolidation at from the technical characteristics, organizational (types of vehicles used, organization of the services) and the geographical (lines served). This approach has allowed us to highlight the speci
Keywords: African Research